Effect of trigger point acupuncture on pain and functional activity in patients with chronic non-specific low back pain: a randomised controlled trial. Issue 3 (June 2023) - Liu, Hong; Li, Ya-Ping; Hou, Mei-Jin; Huang, Wu-Jie; Chen, Xiao-Lin; Gao, Zhen; Jiang, Zheng
Background: Trigger point (TrP) acupuncture is commonly used to treat chronic non-specific low back pain (CNLBP). Evidence for the efficacy of most TrP acupuncture modalities is weak or lacking. Objective: To assess the effect of TrP acupuncture on pain, disability, gait and muscle activation in patients with CNLBP. Methods: From May 2019 to February 2020, a randomised, single-blind clinical trial was carried out involving 33 participants with CNLBP, divided into one of two intervention groups or a control group ( n = 11 per group). The intervention groups received TrP acupuncture or traditional acupuncture treatment three times a week for 4 weeks, and the control group remained on a waiting list and received no treatment. Pain, disability, gait and muscle activation were assessed at baseline and at 4 and 8 weeks of follow-up. Results: At baseline, the three groups showed no significant differences in age, gender, height, weight, body mass index (BMI) or disease course ( p ⩾ 0.05). At 4 weeks, pain was relieved (measured by visual analogue scores, p = 0.036) and disability was improved (reflected by lower Oswestry disability index scores, p = 0.029) in TrP acupuncture versus waiting list groups. Moreover, lumbar extension range of motion was increased in TrP acupuncture versus both traditional acupuncture and waiting list groups ( p = 0.029 and p = 0.027, respectively). At 8 weeks, there were no significant differences in any parameter between the three groups ( p > 0.05). Conclusion: TrP acupuncture had a significant short-term effect on pain relief and disability in patients with CNLBP, but there was no evidence of a long-term influence (at 8 weeks following the intervention). Further high-quality randomised controlled trials are needed for verification in the future. Trial registration number: ChiCTR1900022838 (Chinese Clinical Trial Registry)